Academic development through a pandemic crisis: Lessons learnt from three cases incorporating technical, pedagogical and social support - Sumer, Murat; Douglas, Tracy; Sim, Kwong Nui (Journal of University Teaching and Learning Practice, 2021)
Distance or online learning is more than simply uploading and delivering learning resources to learners but in fact, it is a process that provides learners with autonomy, responsibility, flexibility and choice. This can be a challenge for many academic teachers. In 2020, as universities globally shifted to online learning, in response to the impact of the COVID-19 pandemic, a variety of staff have supported colleagues to develop e-learning techniques ‘just-in-time’ for effective delivery to students in fully online platforms. This has required a transformation of educational development and faculty support globally. This paper will reflect on mechanisms of support demonstrating tailored staff support to transform education in three case scenario contexts, during the impact of the COVID-19 pandemic in three different countries. Our case studies illustrate that support lies beyond technological capability building to also incorporate the essentials of holistic well-being and resilience reinforcement. This paper demonstrates temporary solutions to a global crisis in online education and reflects on lessons learnt and how e-teaching and e-learning support may transform beyond the pandemic.